2011
DOI: 10.1016/j.jvs.2011.03.227
|View full text |Cite
|
Sign up to set email alerts
|

The Scandinavian Propaten® Trial – 1-Year Patency of PTFE Vascular Prostheses with Heparin-Bonded Luminal Surfaces Compared to Ordinary Pure PTFE Vascular Prostheses – A Randomised Clinical Controlled Multi-centre Trial

Abstract: Introduction: Is it possible by pharmacological methods to attenuate the expansion rate of abdominal aortic aneurysms?Method: An Internet-based systematic literature search was performed to identify published reports on pharmacological methods to influence aneurysmal expansion rate.Results: Of an original 450 articles, 22 remained to review: they included 15 cohort studies with 12,321 patients and seven randomised clinical trials (RCTs) with 1546 patients. Most studies are performed without a pre-study sample … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 0 publications
1
40
0
1
Order By: Relevance
“…13 overall, primary patency after 1 year was 86.4% for hb-PtFe grafts and 79.9% for PtFe grafts. secondary patency was 88% in the hb-PtFe graft group and 81% in the other.…”
Section: Conventional Polytetrafluoroethylene Graftsmentioning
confidence: 85%
“…13 overall, primary patency after 1 year was 86.4% for hb-PtFe grafts and 79.9% for PtFe grafts. secondary patency was 88% in the hb-PtFe graft group and 81% in the other.…”
Section: Conventional Polytetrafluoroethylene Graftsmentioning
confidence: 85%
“…Patients were considered for recruitment if they required a femorofemoral bypass graft or a prosthetic femoropopliteal bypass graft as determined by angiography and lack of availability of a venous conduit. Details of the trial have been published previously. Briefly, the primary endpoint was primary patency at 1‐year follow‐up, and patients were recruited and randomized in a ratio of 1 : 1, stratified by centre, to either a Hb‐PTFE (Propaten®) or a standard PTFE graft from the same manufacturer (W. L. Gore & Associates, Flagstaff, Arizona, USA).…”
Section: Methodsmentioning
confidence: 99%
“…The primary outcome of the randomized trial was graft patency at 12 months, as reported previously. The principal longer‐term outcome was graft patency at 5 years.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nach 1 Jahr waren die primären und sekundären Offenheitsraten in der Gruppe der verstärkten Prothesen signifikant besser (55 % und 58 % vs. 42 % und 47 %), für den Extremitätenerhalt ergaben sich jedoch keine signifikanten Unterschiede (nach 1 Jahr 75 % mit und 69 % ohne Support). In der skandinavischen randomisierten Propaten ® -Studie (Lindholt et al 2011) schließlich wurden heparingebundene PTFE-Prothesen mit gewöhnlichen PTFE-Prothesen verglichen. Die Bypässe wurden an die tibialen Gefäße angeschlossen und die Heparin-PTFE-Prothesen über einen autologen Venenpatch distal anastomosiert.…”
Section: Synthetische Bypässe Bei CLIunclassified